2016
DOI: 10.3390/su8121238
|View full text |Cite
|
Sign up to set email alerts
|

Social Farming in the Promotion of Social-Ecological Sustainability in Rural and Periurban Areas

Abstract: Abstract:Rural areas are facing a spectrum of landscape changes and vulnerability as a consequence of financial and environmental crises. Innovative approaches are required to maintain the provision of social services and manage ecosystem services in these areas. We explore the capacity of social farming to create viable and sustainable rural and periurban areas according to a social-ecological perspective. We use the key elements of social-ecological systems under social farming practices to analyse (1) the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 47 publications
5
43
0
8
Order By: Relevance
“…Landscape services (a specification of ecosystem services appropriate for use in landscape governance, [16]) play a central role in several of the contributions to this special issue. García-Llorente et al [17] consider landscape services as provided by social farming, including food production, agrobiodiversity, the preservation of local varieties, and aspects of human health. Berkowitz and Medley [18] express the values that home gardeners experience as services, for example, in terms of enjoying species, inspirational, and health benefits.…”
Section: Social-ecological Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Landscape services (a specification of ecosystem services appropriate for use in landscape governance, [16]) play a central role in several of the contributions to this special issue. García-Llorente et al [17] consider landscape services as provided by social farming, including food production, agrobiodiversity, the preservation of local varieties, and aspects of human health. Berkowitz and Medley [18] express the values that home gardeners experience as services, for example, in terms of enjoying species, inspirational, and health benefits.…”
Section: Social-ecological Systemsmentioning
confidence: 99%
“…Opdam and Steingrover [19] discuss how and why companies may get involved in governance networks in their region, thus extending the formal and non-formal types of governing with a market-based mechanism. Also, Garcia-Llorente et al [17] observed that governance networks for social farming were partly based on market-based mechanisms. What the special issue illustrates is that sustainable landscape management requires innovations in the type of governance in which the traditional top-down steering by the government (based on rules and legislation) is (partly) replaced by a diversity of governance networks, with new partners and mixed governance mechanisms.…”
Section: Landscape Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Historically, this region was commonly referred to as the "orchard" of Madrid due to its agriculture and freshwater availability (Table 1). To support the development of sustainable solutions that deal with emerging water scarcity issues, a participatory strategy is being implemented for agroecosystems beyond market instruments [44,45]. WaterSES is also addressing different institutional settings that govern water resources using cases in Idaho and Texas [46].…”
Section: Sustainability Challenge 2: Using Social-ecological Knowledgmentioning
confidence: 99%
“…It is generally assumed that social farming is a form of farming focused on the community, satisfying its social needs, acting for the benefit of social inclusion of people and groups at risk of exclusion. Such activities are most commonly executed in the form of care or educational farms, which constitute a part of the broadly understood social farming (Di Iacovo, 2009;Kinsella at al., 2014;García-Llorente at al., 2016).…”
Section: Introductionmentioning
confidence: 99%